Pengaruh Aromaterapi Bergamot (Citrus Bergamia) Terhadap Depresi Post Partum - Sujawaty, Sri; Olii, Nancy; Yulianingsih, Endah; Podungge, Yusni; Rasyid, Puspita Sukmawaty (JIDAN Jurnal Ilmiah Bidan, 2024)
Background : Depression postpartum is a mental health disorder that arises after giving birth. Postpartum Depression after giving birth can be more severe and last longer than "baby blues". Aromatherapy with bergamot (Citrus bergamia) contains 38% limonene, 28% linalyl acetate, 8% linalool, 8% gamma-terpinene, and 7% beta-pinene. Linalool has a calming effect, while linalyl acetate can relieve pain and increase feelings of euphoria. Bergamot aromatherapy is known to have antidepressant, relaxing, calming and anxiety-reducing effects. Objective : This study aims to evaluate whether bergamot aromatherapy has an impact on the level of maternal depression after giving birth at the Limboto Community Health Center, Gorontalo Regency. Method: This research is quantitative research using methods quasi-experiment, namely pre and post tests without treatment, the population is all mothers postpartum at the Limboto Community Health Center, Gorontalo Regency, the measuring instrument used in this research was the Edinburgh Postnatal Depression Scale (EPDS) questionnaire and univariate and bivariate data analysis using the Paired T-test with a significance level of ≤0.05. Results : statistical test shows a p-value of 0.000 (≤0.05), this explains that there is a significant effect of bergamot aromatherapy intervention on the level of postpartum maternal depression. Conclusion : Bergamot aromatherapy is effective in reducing postpartum depression and is relevant for culturally and spiritually based healthcare services. As a recommendation, it is hoped that health workers at the Limboto Community Health Center, Gorontalo Regency can do it adopted the use of bergamot aromatherapy as part of a routine intervention program in services for postpartum mothers